Improving English Vocabulary Throught Digital Storytelling For Young Learners At Apple Tree Pre-School Samarinda - yusviani indar maya; abdul rohman; Godefridus Bali Geroda (Wadah Inovasi Indonesia, 2023)
Background: English is an important language for Indonesians to communicate, Indonesian government realizes that learning English must be implemented early because children can catch new information and vocabulary faster in learning English (Cahyati & Madya, Zein, Sukyadi, 2019). Methodology: The methode of the study was classroom action research (CAR). There were two cycles; each cycle consisted of four steps, they were planning, action, observation, and reflection. Findings: The subjects in this study 13 students. The result of the study shows that the using of digital storytelling to improve students’ vocabulary of the Nursery Papaya at Apple Tree Pre-school Samarinda in the academic year of 2022/2023 was successful. Conclusion: The students who passed the passing grade improved gradually from cycle 1 and cycle II. The pre-test 1 score is 63.84 and the percentage of passing criteria is 53.84%. Cycle 1 shows that the post-test score is 77.69 and the percentage of the passing grade is 69.23%. Meanwhile, cycle II shows that pre-test is 80 and the percentage of passing criteria is 76.92% and the post-test score is 90.76 with the percentage of passing grade is 100%. Originality: In this study shows that the use of digital storytelling in increasing vocabulary in young learners is successful.